Respuesta :
Answer:
x = 1/6 =0.167
Step-by-step explanation:
Rearrange:
Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :
3*x+4-(9*x+3)=0
Step by step solution :
Step 1 :
Solving a Single Variable Equation :
1.1 Solve : -6x+1 = 0
Subtract 1 from both sides of the equation :
-6x = -1
Multiply both sides of the equation by (-1) : 6x = 1
Divide both sides of the equation by 6:
x = 1/6 = 0.167
One solution :
x = 1/6 = 0.167
Answer:
1/6
Step-by-step explanation:
Step 1: Subtract 9x from both sides.
3x+4−9x=9x+3−9x
−6x+4=3
Step 2: Subtract 4 from both sides.
−6x+4−4=3−4
−6x=−1
Step 3: Divide both sides by -6.
−6x -1
------- = ----------
-6 -6
x=1/6